(untitled) (Pakistan Journal of Scientific Research, 2024)
Pakistan’s taxation system encounters several significant challenges, including a low tax-to-GDP ratio, pervasive tax evasion and avoidance, inadequate tax administration and compliance, lack of transparency and accountability, inefficient data management and verification processes, as well as instances of corruption and fraud. These challenges have adverse effects on revenue collection, economic growth, public service delivery, and public trust in the government. Corda, a blockchain platform designed for DeFi, offers features such as privacy, scalability, and interoperability that can be leveraged to enhance transparency and efficiency in tax administration. Additionally, this peer-to-peer and permissioned DLT can provide a secure platform for the storage and transfer of tax-related information, reducing the risk of data breaches and fraud. This research explores the potential of Corda blockchain technology for streamlining the taxation system in Pakistan. The research suggests that Corda blockchain technology can play a vital role in enhancing transparency and efficiency in Pakistan’s taxation system, which can ultimately lead to increased tax revenues and a stronger economy. This framework includes integrating tax-related data and processes onto the Corda DLT network, establishing smart contracts for tax transactions, and creating a transparent and auditable tax ecosystem using AMQP/1.0 over TLS. The research also discusses potential challenges and limitations associated with implementing Corda DLT in Pakistan’s taxation system.